2019
DOI: 10.1029/2019gl083442
|View full text |Cite
|
Sign up to set email alerts
|

Jovian Injections Observed at High Latitude

Abstract: The polar orbit of Juno at Jupiter provides a unique opportunity to observe high‐latitude energetic particle injections. We measure energy‐dispersed impulsive injections of protons and electrons. Ion injection signatures are just as prevalent as electron signatures, contrary to previous equatorial observations. Included are previously unreported observations of high‐energy banded structures believed to be remnants of much earlier injections, where the particles have had time to disperse around Jupiter. A model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…These authors found no injection signatures inside of Io's L‐positions. While we do not know why we are seeing such injections and Dumont et al (2015) did not, we do know that injections observed in situ do not necessarily show up in auroral images (Haggerty et al, 2019). Also, there may be something about the innermost environment that suppresses such auroral manifestations.…”
Section: In Situ Characterizationmentioning
confidence: 71%
See 1 more Smart Citation
“…These authors found no injection signatures inside of Io's L‐positions. While we do not know why we are seeing such injections and Dumont et al (2015) did not, we do know that injections observed in situ do not necessarily show up in auroral images (Haggerty et al, 2019). Also, there may be something about the innermost environment that suppresses such auroral manifestations.…”
Section: In Situ Characterizationmentioning
confidence: 71%
“…But, what we can say is that during PJ22 (Figure 9), dynamic injections had recently populated the regions near and even inside Io's orbit ( R = 5.9 RJ). Dynamic injections have been characterized in more distant regions by Mauk et al (1999) and in regions as planetward as L = 7 using Juno by Haggerty et al (2019). One small‐scale injection event studied by Thorne et al (1997), and labeled an “interchange event,” occurred just outside of Io's orbit, at about L = 6.02.…”
Section: In Situ Characterizationmentioning
confidence: 99%
“…The inward‐moving fluxtubes containing energetic particles are often called “injections.” Such injections of energetic particles have been observed in the Io‐Europa environment (Haggerty et al, 2019; Mauk et al, 1999) and are clearly a major element in radial transport within these regions. The structures are much broader in scale than the events observed in magnetometer data by Russell et al (2005), and their dispersion in energy suggests such structures have aged (presumably as they travelled inward).…”
Section: Plasma Torusmentioning
confidence: 71%
“…Pertinent to this work, “auroral injection” events are transient auroral structures occurring between the main auroral oval and the footprint of Io. These auroral structures are thought to be the consequence of energetic particles injected toward the planet in the middle magnetosphere (Haggerty et al, 2019; Mauk et al, 1997, 2002). An understanding of auroral injections is crucial for understanding plasma transport in the magnetosphere and the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma injections are a key consequence of magnetic dipolarizations at Earth (Gabrielse et al, 2016; Ohtani et al, 2007), but such a connection for Jupiter is not yet confirmed by observations. Auroral injection signatures are a counterpart of magnetospheric plasma injections at Jupiter (Dumont et al, 2014; Haggerty et al, 2019; Mauk et al, 2002). Haggerty et al (2019) have also revealed that a plasma injection does not always produce an auroral injection signature.…”
Section: Introductionmentioning
confidence: 99%